Pengembangan Bahan Ajar Berbasis 3D Augmented Reality (3D AR) Menggunakan Model Contextual Teaching and Learning (CTL) untuk Meningkatkan Keterampilan Menyimak Siswa Kelas 8 di MTsN 3 Mojokerto. - Syofia Fadila Nesti; Diana Fitri Aimmah; Ammar Zainuddin (Learning, Media and Technology in Arabic Education, 2026)
The limited availability of interactive listening materials and the continued reliance on printed worksheets and teacher-centered instruction have constrained the development of Arabic listening skills among junior secondary students. This study aimed to develop 3D Augmented Reality-based Arabic instructional materials through the Contextual Teaching and Learning approach, examine their feasibility, evaluate changes in students’ maharah istima’ achievement, and identify students’ responses to their use. The study employed a Research and Development design using the ADDIE model, comprising analysis, design, development, implementation, and evaluation, and incorporated a one-group pretest-posttest design. The participants were Grade 8-E students at MTsN 3 Mojokerto, selected through purposive sampling. Data were collected using expert-validation sheets, listening achievement tests, student-response questionnaires, and implementation documentation, and were analyzed through descriptive statistics, paired-samples testing, the Wilcoxon signed-rank test, and normalized gain analysis. The developed materials were judged feasible for classroom use after revisions based on expert feedback. The paired-samples test showed a statistically significant difference between pretest and posttest scores, t(26) = −2.450, p = .021, while the Wilcoxon test also indicated a significant difference, Z = −2.100, p = .036. The mean N-Gain score was .6315, equivalent to 63.15%, and was classified as moderate, while students responded positively to the materials in terms of interactivity, visual appeal, and learning engagement. These findings indicate that integrating 3D AR with contextual pedagogy can provide a feasible and meaningful alternative for supporting Arabic listening instruction, although broader controlled studies are needed to confirm its effectiveness.